Climate change-related distributional range shifts of venomous snakes: a predictive modelling study of effects on public health and biodiversity - Martinez, Pablo Ariel (2024)
Background. Climate change is expected to have profound effects on the distribution of venomous snake species, including reductions in biodiversity and changes in patterns of envenomation of humans and domestic animals. We estimated the effect of future climate change on the distribution of venomous snake species and potential knock-on effects on biodiversity and public health. Methods. We built species distribution models based on the geographical distribution of 209 medically relevant venomous snake species (WHO categories 1 and 2) and present climatic variables, and used these models to project the potential distribution of species in 2070. We incorporated different future climatic scenarios into the model, which we used to estimate the loss and gain of areas potentially suitable for each species. We also assessed which countries were likely to gain new species in the future as a result of species crossing national borders. We integrated the species distribution models with different socioeconomic scenarios to estimate which countries would become more vulnerable to snakebites in 2070. Findings. Our results suggest that substantial losses of potentially suitable areas for the survival of most venomous snake species will occur by 2070. However, some species of high risk to public health could gain climatically suitable areas for habitation. Countries such as Niger, Namibia, China, Nepal, and Myanmar could potentially gain several venomous snake species from neighbouring countries. Furthermore, the combination of an increase in climatically suitable areas and socioeconomic factors (including low-income and high rural populations) means that southeast Asia and Africa (and countries including Uganda, Kenya, Bangladesh, India, and Thailand in particular) could have increased vulnerability to snakebites in the future, with potential effects on public human and veterinary health. Interpretation. Loss of venomous snake biodiversity in low-income countries will affect ecosystem functioning and result in the loss of valuable genetic resources. Additionally, climate change will create new challenges to public health in several low-income countries, particularly in southeast Asia and Africa. The international community needs to increase its efforts to counter the effects of climate change in the coming decades.